2003
DOI: 10.1113/jphysiol.2003.050153
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transcranial magnetic stimulation on single‐unit activity in the cat primary visual cortex

Abstract: Journal of Physiologytimed combinations of TMS and visual stimuli to analyse the interaction between TMS and sensory evoked activity at the cortical level. METHODS General proceduresUnder deep anaesthesia induced by a combination of ketamine (20 mg kg _1 I.M., Ketanest, Parke-Davies, Germany) and xylazine (2 mg kg _1 I.M., Rompun, Bayer, Germany), cats (n = 7) were fixed into position using standard stereotaxic methods. All incisions and pressure points were also locally anaesthetised by xylocaine (2 %, Astra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
161
3
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(189 citation statements)
references
References 56 publications
21
161
3
4
Order By: Relevance
“…2A, we depict spatially averaged activities in response to both single-pulse and 10-Hz TMS conditions as a mean across nine different cat experiments. Generally, the first TMS pulse led to brief excitation followed by immediate suppression (with duration of 250 ms ± 40 SD), similar to that observed earlier with extracellular electrode recordings using suprathreshold 1-Hz TMS (36). Levels of rebound activity after repetitive single-pulse TMS remained at low values (1.3 ± 0.9 SEM, ×10 −4 ΔF/F), whereas the stepwise increase in activity after 10 Hz rTMS produced significantly higher amplitudes (5.6 ± 1.6 SEM, ×10 −4 ΔF/F).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…2A, we depict spatially averaged activities in response to both single-pulse and 10-Hz TMS conditions as a mean across nine different cat experiments. Generally, the first TMS pulse led to brief excitation followed by immediate suppression (with duration of 250 ms ± 40 SD), similar to that observed earlier with extracellular electrode recordings using suprathreshold 1-Hz TMS (36). Levels of rebound activity after repetitive single-pulse TMS remained at low values (1.3 ± 0.9 SEM, ×10 −4 ΔF/F), whereas the stepwise increase in activity after 10 Hz rTMS produced significantly higher amplitudes (5.6 ± 1.6 SEM, ×10 −4 ΔF/F).…”
Section: Resultssupporting
confidence: 63%
“…In contrast to imaging of blood oxygen level-dependent (BOLD) signals, which are inevitably slow because of their dependence on hemodynamics, we here measured neuronal activity directly as voltage changes across neuronal membranes. Commonly, immediate detection of the fluctuations in neuronal membrane potentials suffers from artifacts introduced by the TMS coil discharge, leading to overload of recording amplifiers around the time point of TMS pulses (22,36) and masking of neuronal effects, which can gradually be reduced by only advanced technologies (50)(51)(52)(53). Obviously, VSD imaging does not provide single-cell resolution and is limited to cortical surface areas.…”
Section: Discussionmentioning
confidence: 99%
“…7 B and C) can be explained by an increased difference in the activity of these two sets of neurons under the assumption that excitation by TMS allows neurons' intrinsic response nonlinearity to amplify any preexisting biases in activity (25). As noted above, disrupted proactive control can be explained by a reduction of bias caused by the long-term inhibitory effects of SEF stimulation in the previous trial (24) (Fig. 7A).…”
Section: Discussionmentioning
confidence: 99%
“…TMS of the occipital lobe excites cortical neurons (Moliadze et al, 2003) to create a retinotopically localized illusory visual percept known as a phosphene (Barker et al, 1985b;Meyer et al, 1991). Many studies have shown that TMS, at intensities above the threshold to induce phosphenes, interferes with normal visual processing and impairs the detection of visual stimuli (Amassian et al, 1989;Kammer, 2007;Harris et al, 2008).…”
Section: Introductionmentioning
confidence: 99%